The Epistemological Teacher-beliefs Towards the Implementation of Written Corrective Feedback (WCF) in ELT: A Systematic Literature Review - Manafe, Thedy Hardi; Hoinbala, Festif Rudolf (Journal of Language, Education, Literature, and Culture, 2024)
Epistemological beliefs are "individual interpretations (beliefs) about knowledge and understanding," Epistemological teachers' beliefs refer to instructors' views on how knowledge is acquired. Teachers' EB is essential in how a teacher evaluates knowledge, justifies the organization and source of information, and, more broadly, how the learning process develops. Therefore, this Systematic Literature Review (SLR) study aims to explore the epistemological beliefs of teachers or educators in the implementation of Written Corrective Feedback in English Language Teaching (ELT) context from multiple existing literatures. There are various results found in this study, such as that the epistemological beliefs cover four categories: necessity and effectiveness, focus, strategy, and scope, teachers' and students' responsibility in WCF, and the teachers' epistemological beliefs in the term of giving WCF in order to improve students writing skills in ELT context.